1996
DOI: 10.1063/1.470899
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on pairwise hydrophobic interactions of methane-like particles: A molecular dynamics study of free energy

Abstract: The association of a pair of hydrophobic solutes in water has been investigated by free energy molecular dynamics simulations of a system containing 516 water molecules. Convergence of the calculations is guaranteed by the comparison of data obtained with two independent free energy sampling techniques, which have been optimized for our system. Coulomb interactions have been treated with the Ewald method. Using this computationally expensive approach many of the previously reported discrepancies in the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
114
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 32 publications
16
114
2
Order By: Relevance
“…As a consequence, the hydrophobic force on the hydrophobes (measured by the negative gradient of the PMF) is also reduced by increasing the temperature. In contrast, it has been shown that the molecular hydrophobic interaction between two methane molecules becomes slightly stronger with increasing the temperature [16].…”
Section: Fig 1 (Color) (A)mentioning
confidence: 84%
See 3 more Smart Citations
“…As a consequence, the hydrophobic force on the hydrophobes (measured by the negative gradient of the PMF) is also reduced by increasing the temperature. In contrast, it has been shown that the molecular hydrophobic interaction between two methane molecules becomes slightly stronger with increasing the temperature [16].…”
Section: Fig 1 (Color) (A)mentioning
confidence: 84%
“…2 that to form a one water-layer size nanobubble, the work of formation amounts to about 65k B T (where k B is the Boltzmann constant). As a comparison, the barrier to dissociation for a methane pair (corresponding to intermolecular distance about 6 A) in water is on the order of 1k B T [4,15,16]. Moreover, the midrange hydrophobic interaction is more than twice longer in range than that of molecular hydrophobic interaction between the methane pair.…”
Section: Fig 1 (Color) (A)mentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, they are seen as an important driving force with regard to the folding of proteins [4,5,6]. Consequently, a wealth of studies of hydrophobic interactions using molecular simulation techniques have been undertaken over the past three decades [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Simulation studies have revealed that the contact state of a pair of hydrophobic particles in aqueous solution is entropically stabilized at ambient conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%